Underminerer naturaliseringsprogrammet demokratiet? De danske naturaliseringskrav i lyset af Habermas’ demokratiteori - Jørgensen, Simon Laumann (Politik, 2014)
The group of Danish non-citizens is large due to strict naturalization demands. Are these demands reason- able? Speci cally, do they undermine their own ends if we evaluate the demands in light of the fact that successful applicants gain full democratic rights? In light of Habermas’ description of autonomy as the central democratic virtue, the paper discusses whether the demands stimulate the central citizenship virtue here de ned as ‘democratic autonomy’; a theoretical ideal which ts in the Danish case. Based on a sceptical evaluation of the naturalization demands in general and of the Danish language test in speci c, the paper discusses the merits of a possible alternative naturalization program. is program is also sketched on the basis of Habermasian ideas.